2020
DOI: 10.3390/molecules25235541
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Characteristics of Lavender Extract and Essential Oil from Lavandula angustifolia Mill.

Abstract: Lavender and its products have excellent flavor properties. However, most studies focus on the aroma profiles of lavender essential oil (LEO). The volatiles in lavender extracts (LEs), either in volatile compositions or their odor characteristics, have rarely been reported. In this study, the odor characteristics of LEs and LEO were comprehensively investigated by gas chromatography-mass spectrometry (GC-MS), coupled with sensory evaluation and principal chemical analysis (PCA). In addition, the extraction con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…The highest percentages of linalool; linalool acetate and lavandulol; lavandulol acetate and terpinen-4-ol were confirmed in the cases of L-Pl-E (17.02; 25.68; 1.40, 3.96 and 6.02%, respectively) ( Table 1 ). Lavandulol and its acetate are of a great interest in the cosmetic and perfumery industries, as it gives the oil a rosaceous, sharp floral aroma [ 36 , 37 ]; thus, their higher levels in natural oil can strongly increase its price. Together with linalool, linalyl acetate, terpinen-4-ol, and α-terpineol—the compounds were recently selected to study the influence of long-term storage on essential oil content and in the quality of two Czech Lavandula angustifolia Mill.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest percentages of linalool; linalool acetate and lavandulol; lavandulol acetate and terpinen-4-ol were confirmed in the cases of L-Pl-E (17.02; 25.68; 1.40, 3.96 and 6.02%, respectively) ( Table 1 ). Lavandulol and its acetate are of a great interest in the cosmetic and perfumery industries, as it gives the oil a rosaceous, sharp floral aroma [ 36 , 37 ]; thus, their higher levels in natural oil can strongly increase its price. Together with linalool, linalyl acetate, terpinen-4-ol, and α-terpineol—the compounds were recently selected to study the influence of long-term storage on essential oil content and in the quality of two Czech Lavandula angustifolia Mill.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds showed the widest spectrums of activity among the components included in the present study, also identified elsewhere in L. angustifolia Mill. [ 37 ]. All included reference substances had bactericidal (MBC/MIC = 1–4) and fungicidal effects (MFC/MIC = 1–4).…”
Section: Discussionmentioning
confidence: 99%
“…It's also called as English lavender and it finds its place in all the restaurants and kitchens where it is used as a flavoring agent and for seasoning purposes and cosmetic industry. Wang et al [17] [19] examined the essential oils of lavender to provide protection against neural disorder like Alzheimer disease and dementia, it shows improved cognitive performance against epilepsy and convulsions in animals and human subjects and they are cheap, easy to obtain and safe to use with good efficiency. Oran et al [20] inferred the methanolic extracts of Lavendula angustifolia Mill.…”
Section: Aromatic Profiling In Lavendula Angustifoliamentioning
confidence: 99%
“…Methods used to ensure batch-to-batch consistency of the herbal compound/s being investigated are mass spectrometry and high-performance liquid chromatography (HPLC). Spectrometry has been used to evaluate individual herbs [ 27 , 28 ], and HPLC has been used for herbal formulas containing a number of compounds, thereby providing reliable and reproducible findings regarding their safety and efficacy in the oncology setting (e.g., the herbal formulas PHY906 and LCS101 [ 29 , 30 ]).…”
Section: Safety Of Herbal Medicine Use In Oncologymentioning
confidence: 99%